Role of anthraquinones in combating insulin resistance - Wanru Xia; Shuqian Li; LinZehao Li; Shibo Zhang; Xiaolei Wang; Wenyu Ding; Lina Ding; Xiandang Zhang; Zhibin Wang (Frontiers Media S.A., 2023)
Insulin resistance presents a formidable public health challenge that is intricately linked to the onset and progression of various chronic ailments, including diabetes, cardiovascular disease, hypertension, metabolic syndrome, nonalcoholic fatty liver disease, and cancer. Effectively addressing insulin resistance is paramount in preventing and managing these metabolic disorders. Natural herbal remedies show promise in combating insulin resistance, with anthraquinone extracts garnering attention for their role in enhancing insulin sensitivity and treating diabetes. Anthraquinones are believed to ameliorate insulin resistance through diverse pathways, encompassing activation of the AMP-activated protein kinase (AMPK) signaling pathway, restoration of insulin signal transduction, attenuation of inflammatory pathways, and modulation of gut microbiota. This comprehensive review aims to consolidate the potential anthraquinone compounds that exert beneficial effects on insulin resistance, elucidating the underlying mechanisms responsible for their therapeutic impact. The evidence discussed in this review points toward the potential utilization of anthraquinones as a promising therapeutic strategy to combat insulin resistance and its associated metabolic diseases.